Deformation compatibility formed grinding method of flexible gear - WANG SHUIMING; WANG CHUNMING; XU QIANG; DOU YONGQIANG; ZHENG JIGUI; SHI WEI (2016)
A deformation compatibility formed grinding method of a flexible gear comprises following steps: firstly, a mechanical machining method is adopted to machine a flexible gear tooth blank, the tooth crest of the un-machined section of flexible gear teeth is arranged inwards to form taper, the taper angle a is equal to arctan(w/L), w is the radial deformation amount of the long axis of a wave generator, and L is a flexile gear cylinder length; secondly, the wave generator is loaded in the preset position of an inner cavity of the flexible gear and is fixed, and one side of a flexible gear output flange is connected with a dividing apparatus; thirdly, the device mounted in the second step is integrally mounted on a platform of a grinding machine, and the long axis of the wave generator is perpendicular to the above platform; and fourthly, the outline center of a formed grinding wheel on the grinding machine is aligned with the long axis of the wave generator and then begins to be subject to radial grinding, after